Characterization of honey from West and South Buenos Aires province, Argentina - Valle, A.; Andrada, A.; Aramayo, E.; Gil, M.; Lamberto, S. (Spanish Journal of Agricultural Research, 2004)
Pollen analyses were carried out on 33 honey samples from Espinal, Monte de Llanuras y Mesetas and Pampeana phytogeographical Provinces, collected during the 2000-2001 period. Sample processing as well as qualitative and quantitative analyses were performed according to standard techniques. Sixty-seven morphological pollen types were identified. The association of Eucalyptus sp. (E. camaldulensis Dehnh., E. viminalis Labill.), Centaurea sp. (C. solstitialis L., C. calcitrapa L.) and Diplotaxis tenuifolia DC. characterized these honeys. Twelve samples were unifloral: six from Eucalyptus sp., five from Helianthus annuus L., and one from Brassicaceae. Asteraceae and Fabaceae were the most representative botanical families.